1997
DOI: 10.1111/j.1469-7610.1997.tb01537.x
|View full text |Cite
|
Sign up to set email alerts
|

A Competency‐based Model of Child Depression: A Longitudinal Study of Peer, Parent, Teacher, and Self‐evaluations

Abstract: In a two-wave longitudinal study of third and sixth graders (N = 617), we obtained self-reports of depression and peer, teacher, parent, and self-reports of competence in five domains: academic, social, attractiveness, conduct, and athletic. Competency evaluations by others predicted change in self-perceived competence over time for girls, but not for boys. Depression predicted change in self-perceived competence over time for boys but not for girls. Among girls, the relative importance of parent, teacher, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(138 citation statements)
references
References 60 publications
4
129
1
1
Order By: Relevance
“…Consistent with our gender-specific findings, Reinherz and colleagues [7] found that poor academic achievement at age 9 was a risk factor for women but not for men. Other research has shown girls to be more sensitive to competency evaluations [32], so it possible that girls may be psychologically more vulnerable to actual failure experiences in the school domain, particularly since they were less common for girls than for boys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our gender-specific findings, Reinherz and colleagues [7] found that poor academic achievement at age 9 was a risk factor for women but not for men. Other research has shown girls to be more sensitive to competency evaluations [32], so it possible that girls may be psychologically more vulnerable to actual failure experiences in the school domain, particularly since they were less common for girls than for boys.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of this, we used teacher reports of depressive problems, which are limited by exposure to one particular context (school) as well as teachers' inability to directly observe the more internal phenomenology of depression. Correlations between teacher reports and self-reports of depression range from .20 to .50 [32,38,39]. Fourth, analyses using the WLSMV estimator were based on the standard untested assumption that a continuous latent response variable that is normally conditioned on the exogenous variables underlies the observed dichotomous outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 presents prospective studies that explore self-perception and depression. Evidence supporting negative self-perception as a proximal vulnerability to depressive symptoms is found in eight (Cole, Jacquez, & Maschman, 2001;Cole, Martin, & Powers, 1997;Cole, Martin, Powers, & Truglio, 1996;Kistner, Balthazor, Risi, & Burton, 1999;Measelle et al, 1998;Ohannessian, Lerner, Lerner, & von Eye, 1999; of the fourteen studies. Mixed evidence is found in three studies (Cole, Martin, Peeke, Seroczynski, & Fier, 1999;Hoffman, Cole, Martin, Tram, & Seroczynski, 2000;Kistner, DavidFerdon, Repper, & Joiner, 2006), with an additional three studies (Cole, Martin, Peeke, Seroczynski, & Hoffman, 1998;Lewinsohn et al, 1994;McGrath & Repetti, 2002) presenting evidence that depression predicts self-perception.…”
Section: Self-perceptionmentioning
confidence: 99%
“…Conversely, a negative cumulation effect was observed such that children with multiple domains in which their teachers, parents, peers, or themselves judged them as incompetent, had higher levels of depressive symptoms than did children with only one incompetent domain. In a related two-wave longitudinal study, third and sixth graders' perceptions of their own competence was found to be predictive of changes in depressive symptoms over time such that an increase in perceived competence corresponded to subsequent decreases in depressive symptoms, whereas a decrease in competence corresponded to an increase in self-reported depressive symptoms (Cole, Martin, & Powers, 1997). Several longitudinal investigations have attempted to examine the causal relationships between these factors, as well as the developmental periods in which academic and social competence influence internalizing and externalizing symptoms (Burt, Obradovic, Long, & Masten, 2008;Burt & Roisman, 2010;Masten et al, 2005).…”
Section: Cole's Competency-based Model Of Child Depressionmentioning
confidence: 99%